Core strength and spectrographic vocal characteristics in women (Research, Society and Development, 2020)
The adequate respiratory support ensures resonance, projection, focus, stability, and better vocal quality. The aim of this study was to verify the relationship between the activation of the core musculature and the spectrographic acoustic vocal characteristics in a group of adult women. This is a cross-sectional, observational, analytical, and quantitative study with ten women 19 to 28 years old, without vocal complaints, and without laryngeal disorders. Spectrographic vocal analysis, maximum expiratory pressure measurement, and evaluation of the multifidus, transverse and perineum muscles were performed. The data were analyzed using the Spearman Correlation Test at 5 %. The results showed significant positive correlation between the maximum expiratory pressure and the definition of the second formant; between the activation of the perineal muscle and the regularity of the spectrographic tracing. And showed significant negative correlation between the activation of the multifidus muscles and the width of the second formant. It was concluded that the more activated the perineal musculature, the greater the regularity of the spectrographic tracing; the higher the maximum expiratory pressure, the greater the definition of the second formant; and the greater the activation of the multifidus muscles, the smaller the bandwidth of the second formant. Such findings demonstrate the role of the core strength in the vocal quality. A relationship was established among the maximum expiratory pressure, the activation of the core muscles, and the spectrographic vocal characteristics.